Neonatal warming devices: What can be recommended for low-resource settings when skin-to-skin care is not feasible? - Kyokan, Michiko; Rosa-Mangeret, Flavia; Gani, Matthieu; Pfister, Riccardo E. (Frontiers in Pediatrics, 2023)
Hypothermia occurs frequently among clinically unstable neonates who are not suitable to place in skin-to-skin care. This study aims to explore the existing evidence on the effectiveness, usability, and affordability of neonatal warming devices when skin-to-skin care is not feasible in low-resource settings. To explore existing data, we searched for (1) systematic reviews as well as randomised and quasi-randomised controlled trials comparing the effectiveness of radiant warmers, conductive warmers, or incubators among neonates, (2) neonatal thermal care guidelines for the use of warming devices in low-resource settings and (3) technical specification and resource requirement of warming devices which are available in the market and certified medical device by the US Food and Drug Administration or with a CE marking. Seven studies met the inclusion criteria, two were systematic reviews comparing radiant warmers versus incubators and heated water-filled mattresses versus incubators, and five were randomised controlled trials comparing conductive thermal mattresses with phase-change materials versus radiant warmers and low-cost cardboard incubator versus standard incubator. There was no significant difference in effectiveness between devices except radiant warmers caused a statistically significant increase in insensible water loss. Seven guidelines covering the use of neonatal warming devices show no consensus about the choice of warming methods for clinically unstable neonates. The main warming devices currently available and intended for low-resource settings are radiant warmers, incubators, and conductive warmers with advantages and limitations in terms of characteristics and resource requirements. Some devices require consumables which need to be considered when making a purchase decision. As effectiveness is comparable between devices, specific requirements according to patients’ characteristics, technical specification, and context suitability must play a primary role in the selection and purchasing decision of warming devices. In the delivery room, a radiant warmer allows fast access during a short period and will benefit numerous neonates. In the neonatal unit, warming mattresses are low-cost, effective, and low-electricity consumption devices. Finally, incubators are required for very premature infants to control insensible water losses, mainly during the first one to two weeks of life, mostly in referral centres.